Does trade cause growth? A policy perspective - Klaus Wälde (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2000)
Several empirical papers have shown that international trade has a positive causal effect on a country's GDP or growth rate. A common conclusion from these results is that a free trade policy will increase a country's GDP. This comment does not dispute the empirical findings per se but questions this conclusion. An example is provided that shows that it is not obvious which policy recommendations can be supported by these empirical findings.
Keywords: 330; Außenwirtschaft; Wirtschaftswachstum; Exportinduziertes Wachstum; Freihandel; Theorie; Welt